Khittah Nahdlatul Ulama: (Pemahaman Makna, Integrasi Politik Dan Jati Diri NU) - Marahalim; Katimin; Harahap, Elly Warnisyah (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2023)
This article aims to analyze the political values ​​of Nahdlatul Ulama (NU) from Khittah's perspective and its position in political practice. The debate occurred because Nahdlatul Ulama was considered to be playing practical politics, and on the other hand, the Nahdlatul Ulama Khittah was always discussed, saying that Nahdlatul Ulama should not enter into practical politics because of the 1926 NU Khittah. The type of research used was library research. Researchers studied documents, books, journals, magazines and various literature related to NU's position on politics in the 1926 NU Khittah and its position in political practice. The results of the research show that there are two meanings of khittah: the “khass” (far'i-juz'i) namely the NU Khittah text resulting from the Situbondo Congress, and the